Inheritance of Human Palmar Dermatoglyphs - Marcinkiewicz, Stanisław (Anthropological Review, 1977)
The author has investigated the main lines (DCBA) together with quantitative dermatoglyphic characters of the human palm on the material comprising palm prints of 168 families. The termination type of the main lines was shown to be heritable (see tables 3, 9, 10). The ridge count in three sub-digital areas: a-b, b-c, c-d, and along the line t-d on the palm is also found to be determined genetically (see respective tables 12 and 7). Sexual dimorphism, as well as differences between the left and right palm, were visible in the ridge count in the case of those ridges that tend to be perpendicular to the longer axis of the hand (table 5). Numbers of ridges occurring in three sub-digital areas and along the t-d line are interrelated (table 8), though palmar ridge count is independent of the number of ridges on fingers.